Peran Dinas Tenaga Kerja dan Transmigrasi Provinsi Jambi dalam Mengurangi Angka Pengangguran Menggunakan Website Sibakol - Nurzahwa, Cindy Lusiana; Marlina, Lilis; Azzahra, Lilisa; Munira, Munira; Jadid, Miftahul; Rizky, Muhammad; Umam, Khotibul; Aini, Quratul (Universitas Pahlawan Tuanku Tambusai, 2024)
This research examines the role of the Jambi Province Manpower and Transmigration Service in reducing unemployment through Sibakol Website innovation. The Sibakol website, as a job search platform, is designed to make it easier for individuals to find suitable job opportunities. This study uses data analysis of registered users on the Sibakol website from 2020 to 2023 to assess its effectiveness in connecting job seekers with available job opportunities. The research results show that Sibakol has made a significant contribution to reducing unemployment rates in Jambi, with an increasing number of Sibakol users who have succeeded in finding work through this platform. Digital innovations such as Sibakol have the potential to become an important tool in local government strategies to overcome unemployment problems and improve community welfare. The research method used is descriptive qualitative with an inductive approach. Data was collected through observation, interviews and documentation. The research results show that the Sibakol Website has made a significant contribution in matching job seekers with available job opportunities, although there are still several obstacles in its implementation. The Department of Manpower and Transmigration plays a role not only as a facilitator but also as a liaison between job seekers and job providers, with the hope of gradually reducing the unemployment rate.